2017
DOI: 10.1021/acs.jpcc.7b07109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noncovalent Interactions on the Catalytic Activity of Unsupported Colloidal Palladium Nanoparticles Stabilized with Thiolate Ligands

Abstract: This article presents the systematic evaluation of colloidal palladium nanoparticles functionalized with well-defined small organic ligands that provide spatial control of the geometric and electronic surface properties of nanoparticle catalysts. Palladium nanoparticles stabilized with thiolate ligands of different structures and functionalities (linear alkyl vs cyclohexyl vs phenyl) are synthesized using the thiosulfate protocol in a two-phase system. The structure and composition of palladium nanoparticles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 54 publications
(150 reference statements)
1
23
0
Order By: Relevance
“…PdNPs capped with constitutional isomers of pentanethiolate ligands were synthesized using the published procedure from our lab with a modified mole ratio of to surfactants (TOAB and alkylthiosulfate) (Maung and Shon, 2017 ). The two-phase method using two equivalents of sodium S-pentyl thiosulfate isomers to palladium metal complex initially yielded nanoparticles with less desirable stability and solubility in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PdNPs capped with constitutional isomers of pentanethiolate ligands were synthesized using the published procedure from our lab with a modified mole ratio of to surfactants (TOAB and alkylthiosulfate) (Maung and Shon, 2017 ). The two-phase method using two equivalents of sodium S-pentyl thiosulfate isomers to palladium metal complex initially yielded nanoparticles with less desirable stability and solubility in organic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…These catalytic reactions take place in homogeneous conditions that normally promote catalytic efficiency and selectivity and complete under the mild condition of room temperature and atmospheric pressure. By introducing various functional groups, such as carboxylic acid and phenyl groups to PdNPs, the previous work has shown that the diverse catalytic platforms for specific chemical interactions could be created (Chen et al, 2017 ; Maung and Shon, 2017 ; Mahdaly et al, 2019 ). The results clearly demonstrated that controlling the partial poisoning of catalytic metal nanoparticle surface with well-defined alkanethiolate ligands bring about the development of highly selective and efficient catalytic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies confirmed the contribution of the p orbitals and planar geometry of the benzene ring in aiding the formation of the di-σ-bonded Pd-alkyl intermediate that is necessary for the hydrogenation process. 26,33,34 To further investigate alkanethiolate-capped PdNP as chemoselective hydrogenation catalysts, m -nitrostyrene was first selected as a control system (Scheme 1). Because the nitro moiety is strongly electron-withdrawing and in general very reactive to Pd catalysts under a hydrogen environment, it was necessary to determine the optimized conditions that provide an efficient hydrogenation activity for less activated alkenes while maintaining high chemoselectivity for hydrogenation of alkene over the nitro group.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the weaker adsorption of styrene on the Pd nanoparticle surface was directly translated to the slower catalytic hydrogenation by PhC2 PdNP and the equilibrium between the substrate and Pd-alkyl intermediate. Based on the previously reported catalytic activity of PdNP generated from 2-cyclohexyl-1-ethylthiosulfate (CyC2 PdNP) that was similar to that of C8 PdNP, 33 the presence of a large phenyl group, which is smaller than the cyclohexyl group, does not seem to cause any significant steric problem on the nanoparticle surface. Hence, different catalytic activities of PhC2 PdNP should mostly arise from the influence of aromatic π–π interactions between surface ligands and substrates.…”
Section: Resultsmentioning
confidence: 99%
“…95,96 Alkanethiolate-capped PdNP and PtNP catalysts have been shown to catalyse regio-, chemo-, and stereoselective organic reactions, with the hydrophobic ligand playing a role in directing activity and selectivity. [97][98][99][100][101][102] Capping the catalytic PdNP and PtNP core with ligands of various functional groups and hybridizing them with lipid assemblies could potentially serve as a model system for enzyme site mimics in addition to above mentioned biocatalysis and bioorthogonal reactions.…”
Section: Discussionmentioning
confidence: 99%